Posouzení nákladů spojených s vytápěním novostavby energeticky úsporného rodinného domu - Šebelová, Denisa (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2021)
Tato diplomová práce se věnuje ekonomickému posouzení způsobů vytápění a kombinací s technologiemi pro úsporu energií. Cílem této práce je zhodnotit ekonomickou efektivitu jednotlivých typů zdrojů vytápění. Nejprve je třeba určit celkovou potřebu energií na vytápění, ohřev teplé vody a chod domácnosti. Na základě těchto informací určit vhodné zdroje. Do posouzení dále vstupují alternativní zdroje energie – řízené větrání s rekuperací odpadního tepla a fotovoltaická elektrárna. Cílem práce je zjistit, jaká kombinace, těchto technologií je pro vybraný dům ekonomicky nejefektivnější variantou. Tato práce má investorovi pomoci v rozhodování o technologickém řešení vytápění a získávání energií. Výsledkem je komplexní zhodnocení různých variant pro posuzovaný rodinný dům.

This diploma thesis addresses the economic assessment of the methods of heating and combinations of technologies for energy saving. The objective of this work is to assess the economical effectiveness of individual types of sources of heating. It is first necessary to established gross requirements of energy for heating, water heating, and other household operations. Based on this information, suitable sources are determined. Alternative energy sources are other aspects for consideration – controlled ventilation with heat recovery, and photovoltaic cells. The aim of the thesis is to identify which combination of those technologies is the most economically effective for the opted house. This work aims to help the investor in decision making about the technological solution of heating and power purchase. The outcome is a complex evaluation of different options for the assessed house.
Assessment of Costs Associated with Heating a New Energy-Efficient House
Keywords: Energeticky úsporný dům; efektivita; tepelné čerpadlo; investice; Energy efficient house; efficiency; heat pump; investment